Development of Lombok Island Environmental Change E-Module to Improve Environmental Literacy and Data Literacy of High School Students - Watoni, Edi Satria; Ngabekti, Sri; Wijayati, Nanik (Journal of Innovative Science Education)
The aims of this study are 1) to determine the characteristics of E-modules; 2) to determine the validity of the E-module; 3) student responses to the E-module; 4) E-module effectiveness in improving student literacy; 5) the practicality of the developed E-module. This type of research is R&D, using the model Brog and Gall. The results showed that the E-module on environmental change on the island of Lombok was declared very valid by expert lecturers with an average percentage, material experts obtained an average score of 77.08% while media experts were 97%. The results of a wide-scale trial of 74 students from each school obtained an average student response of 82%, 82.76% and 83.25%. The results of the N-gain scores from each school showed that there was an increase in student literacy after using the E-module in the learning process, namely 0.64, 0.56, and 0.57. Furthermore, the results of the practicality test questionnaire filled out by biology teachers obtained an average of 82, 82.76 and 83.25 from each school. This study resulted in a valid, effective and practical E-module in improving the Environmental Literacy and Data Literacy of high school students.